Variable Parameters Affecting to Nile Tilapia (Oreochromis Niloticus) Fish-Paste Production - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Tilapia has emerged as one of the most cultivated and marketed species in Vietnam. There is not much research mentioned to processing of fish-paste of this valuable fish. In order to improving the added value of this fish, we investigated a production of fish-paste from Nile tilapia (Oreochromis niloticus). By investigation different parameters probably affecting to gelation, the results was noticed that the best physicochemical properties and sensory characteristics of fish-paste would be obtained by the addition of modified starch 1.5%: guar gum 1.5%. These results demonstrated that the addition of modified starch and guar gum in the formulation of Nile tilapia fish-paste increased the nutritional value of the product without reducing its sensory preference.Keywords: Nile tilapia (Oreochromis niloticus), fish-paste, Modified starch, Guar gum, Physicochemical properties.